2005
DOI: 10.1179/136485905x19937
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism behind the antileishmanial effect of zinc sulphate. II. Effects on the enzymes of the parasites

Abstract: When used in vitro, zinc sulphate has a direct antileishmanial effect. To see if this effect involved the inhibition of the parasites' enzymes, extracts of the promastigotes and axenic amastigotes of Leishmania major (MHOM/IQ/93/MRC6) and L. tropica (MHOM/IQ/93/MRC2) were prepared. Zinc sulphate, at various concentrations, was then added to samples of these extracts before the activities, in the samples, of certain key enzymes of the Embden-Meyerhof pathway, hexose-monophosphate shunt and citric-acid cycle, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Several modes of action for Zn(II) complexes with anti-leishmanial properties have been discussed in the literature: some compounds have been reported to inhibit enzymes essential for the parasite's carbohydrate metabolism, such as those involved in the Embden-Meyerhof pathway. 48 Some studies have indicated that Zn(II) complexes selectively recognize anionic cell surfaces through a combination of electrostatic attraction and specific coordination of the zinc cations with phospholipids in the cell membrane. 49,50 Given the changes in parasite morphology effected by the Zn(II) complexes described herein resulting in loss of the distinct shape of the parasite, a structural component of the parasite membrane could be proposed as a plausible target.…”
Section: -Esi †)mentioning
confidence: 99%
“…Several modes of action for Zn(II) complexes with anti-leishmanial properties have been discussed in the literature: some compounds have been reported to inhibit enzymes essential for the parasite's carbohydrate metabolism, such as those involved in the Embden-Meyerhof pathway. 48 Some studies have indicated that Zn(II) complexes selectively recognize anionic cell surfaces through a combination of electrostatic attraction and specific coordination of the zinc cations with phospholipids in the cell membrane. 49,50 Given the changes in parasite morphology effected by the Zn(II) complexes described herein resulting in loss of the distinct shape of the parasite, a structural component of the parasite membrane could be proposed as a plausible target.…”
Section: -Esi †)mentioning
confidence: 99%
“…Zinc level is important for T cell, neutrophil, and natural killer cell function. The antileishmanial effect of zinc may result from the inhibition of enzymes that are necessary for the parasites, and these effects are dose dependent [13]. Our study results showed that both treatments (ZS and MA) have moderate cure rate in CL.…”
Section: Discussionmentioning
confidence: 67%
“…In CL, macrophages engulf Leishmania amastigotes which divide inside them [19]. Zinc is known to influence macrophage function [20].…”
Section: Role Of Zinc In Host Immunitymentioning
confidence: 99%
“…Zinc sulfate has a significant inhibitory effect on key enzymes involved in the carbohydrate metabolism and virulence of L. major and L.tropica [20]. The Embden-Meyerhof pathway is one of the important pathways in carbohydrate metabolism.…”
Section: Role Of Zinc In Parasite Metabolism Pathwaymentioning
confidence: 99%
See 1 more Smart Citation